2012
DOI: 10.1021/jf303160y
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Mechanism of Ginsenoside Compound K and Its Butyl and Octyl Ester Prodrugs in Caco-2 Cells

Abstract: Ginsenoside compound K (CK) is a bioactive compound with poor oral bioavailability due to its high polarity, while its novel ester prodrugs, the butyl and octyl ester (CK-B and CK-O), are more lipophilic than the original drug and have an excellent bioavailability. The aim of this study was to examine the transport mechanisms of CK, CK-B, and CK-O using human Caco-2 cells. Results showed that CK had a low permeability coefficient (8.65 × 10(-7) cm/s) for apical-to-basolated (AP-BL) transport at 10-50 μM, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 32 publications
(41 reference statements)
3
41
0
Order By: Relevance
“…6) It has been reported that esterification increases pharmacokinetic properties. Fatty acid esterification of CK increases its absorption and bioavailability, 7) and has a considerable effect on its cytotoxicity against various human cancer cell lines. Although improved efficacies of various ginsenosides has been reported, 8) difficulties in target-based delivery of ginsenosides to tumor sites as well as their poor bioavailability, absorption, and solubility remain major drawbacks to the use of ginsenosides in clinical trials.…”
mentioning
confidence: 99%
“…6) It has been reported that esterification increases pharmacokinetic properties. Fatty acid esterification of CK increases its absorption and bioavailability, 7) and has a considerable effect on its cytotoxicity against various human cancer cell lines. Although improved efficacies of various ginsenosides has been reported, 8) difficulties in target-based delivery of ginsenosides to tumor sites as well as their poor bioavailability, absorption, and solubility remain major drawbacks to the use of ginsenosides in clinical trials.…”
mentioning
confidence: 99%
“…Verapamil and MK-571 are well-known as the inhibitors of P-gp and MRP2, respectively [20]. Ko143, a potent and selective BCRP inhibitor, displays higher than 200-fold selectivity over P-gp and MRP1 transporters [21].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosides are a good substrate for P-gp [26], [27], and it is possible that B-complex vitamins could have enhanced the expression levels of P-gp in intestines, which led to the poorer absorption of ginsenoside Re. Some studies have suggested that the transport mechanism of ginsenosides is passive diffusion [19], [28]; by contrast, the main transport mechanism of B vitamins is active transport [29], [30]. However, because both passive diffusion and active transport require a specific carrier protein, it is possible that B-complex vitamins might interfere in the role of carrier protein of ginsenoside Re.…”
Section: Discussionmentioning
confidence: 99%